LEARNER AUTONOMY PRACTICES IN ENGLISH-SPEAKING CLASSROOMS: AN OBSERVATION AT THE TERTIARY LEVEL LEARNERS IN BANGLADESH - Laila Noor (UICELL, 2021)
Learner autonomy has been playing an essential role in EFL learning for over thirty years. In Bangladesh, English speaking classrooms are mainly teacher-centered, and only limited space on learner autonomy paves the way for this study. The study focuses on the present scenario of practicing learner autonomy in an English-speaking classroom and the challenges of implementation at the tertiary level. In Bangladesh, enormous work has been done on developing English speaking skills, but a few works have been conducted on practicing learner autonomy in an English-speaking classroom. The study was non-experimental research and followed a casual-comparative design. The research used mixed methods for data analysis. In the quantitative approach, descriptive statistics and inferential statistics have been used. The results have been analyzed by SPSS 28.0 (Statistical Package for Social Science) and Microsoft Office excels. For qualitative approach, focused group interview has been done. The findings show that learners' autonomy is not being practiced adequately in an English speaking classroom. Both teachers and learners tend to practice "reactive autonomy" than "proactive autonomy." The study also sheds light on the positive attitude of both learners and teachers on practicing learner autonomy in an English speaking classroom and the challenges of its implementation in the English classroom at the tertiary level. This work can be useful in supporting learner autonomous classroom and will be beneficial for further study. Moreover, the study anticipates further study in this field is necessary.